Small‐signal impedance modelling and stability analysis of doubly fed induction generator‐based wind turbines during asymmetrical weak grid condition - Hailiang Xu; Zhi Li; Han Wu; Qingzeng Yan; Lie Xu (IET Renewable Power Generation)
Abstract Doubly fed induction generator (DFIG)‐based wind turbines (WTs) that connected into weak power grid may lose their stability. However, the stability issue becomes more complex and has not been well addressed during the asymmetric grid scenario, especially when the negative sequence current response is required, according to the latest grid codes. To settle such an issue, a small‐signal impedance model of the DFIG‐based WT with negative‐sequence current control is established in this paper. Based on the proposed model, the interaction mechanism between the DFIG and the imbalanced grid is analysed. The influence of the main physical and control parameters on the system stability is then assessed in detail. It is found that improper design of the notch filters in the control loop may arouse insufficient decoupling between the positive and negative components, which can further deteriorate the system stability and robustness. To cope with the problem, the setting rule of the quality factor of the second‐order notch filter, considering its dynamic and static characteristics, is derived. Simulations and experiments are finally conducted to validate the correctness of the theoretical analysis.